Oxygen Uptake Off-Transient Kinetics Responses to Exercises - Elvin Onarici Gungor, (Journal of Educational Issues, 2024)
The kinetics of oxygen uptake during recovery is defined off-transient kinetics (Sousa et al., 2015). The purpose of this study was to compare the VO2 off-transient kinetics response of physical education students and also compare the different exercise intensities. Physical education students were grouped as males (n = 10) and females (n = 10). Subjects performed an incremental exercise test for the determination of cardiorespiratory responses. Subjects also performed below threshold exercise on different day. Oxygen uptake was tested via CPX Oxygen analyzer. Off-transient kinetics were modelled via mono-exponential model. The group mean of time to exhaustion was shown statistically significant difference 13±0.6 min for woman and 15±1 min for men and also, the group mean of ventilation at peak was shown statistically significant difference 88±10 L min-1 for woman and 127±35 L min-1 for men according to cardiorespiratory responses at peak exercise. Absolute VO2peak (L min-1), VO2peak (ml min-1), relative VO2peak (ml kg-1 min-1), HRmax (bpm), RER at exhaustion was shown no statistically significant difference between gender. The group mean of VO2off (ml kg-1 min-1) was shown statistically significant difference 36±6 for woman and 49±4 for men to the off-transient responses to peak exercise. But time constant of the off-transient response was shown no statistically significant difference (141±20 sec for woman and 127±27 sec for men) between gender. The group mean of VO2off (ml kg-1 min-1) and time constant of the off transient response was shown no statistically significant difference between gender (25±4 ml kg-1 min-1 for woman and 30±3 ml kg-1 min-1 for men; 153±29 sec for woman and 150±30 sec for men) to the off-transient responses to moderate intensity exercise. The group mean of VO2off (ml kg-1 min-1) at maximal exercise was found higher than moderate intensity exercise (p = .040) (43±8 ml kg-1 min-1 at maximal exercise and 27±4 ml kg-1 min-1 at moderate intensity exercise). The group mean of time constant of the off-transient response at maximal exercise was lower than moderate intensity exercise (p = .015) (134±24 sec at maximal exercise, 151±28 sec at moderate intensity exercise). But time constant of the off transient response was shown no statistically significant difference (141±20 sec for woman and 127±27 sec for men) between gender. The group mean of VO2off (ml kg-1 min-1) and time constant of the off transient response was shown no statistically significant difference between gender (25±4 ml kg-1 min-1 for woman and 30±3 ml kg-1 min-1 for men; 153±29 sec for woman and 150±30 sec for men) to the off-transient responses to moderate intensity exercise. The group mean of VO2off (ml kg-1 min-1) at maximal exercise was higher than moderate intensity exercise (p = .040) (43±8 ml kg-1 min-1 at maximal exercise and 27±4 ml kg-1 min-1 at moderate intensity exercise). The group mean of time constant of the off transient response at maximal exercise was lower than moderate intensity exercise (p = .015) (134±24 sec at maximal exercise, 151±28 sec at moderate intensity exercise). These findings indicate that gender and exercise intensities effect the recovery speed by speeding the rate of adjustment of oxidative phosphorylation.